Achieving better peer interaction in online discussion forums: A reflective practitioner case study - Xia, Jianhong (Cecilia); Fielder, John; Siragusa, Lou (Western Australian Institute for Educational Research Inc, 2013)
This paper documents the initial phase of a research project to improve peer interaction in a discussion forum for a Spatial Sciences class (unit) at Curtin University. A number of strategies were implemented to redress the low levels of online participation prevailing for a number of years. Three research questions were formulated to evaluate the effectiveness of teaching and learning initiatives. The analysed statistical data for this unit obtained from Blackboard revealed positive correlations between students’ results and their participation in the discussions forum, which was supported by students’ comments on the forum. The statistical measures used offered a way of ensuring a more objective evaluation of the effectiveness of the changes, with evidence of promising improvements in participation levels. The initiatives of offering incentives to participate in the discussion forum and creating a positive community environment appear to have marginally increased levels of achievement.